Sustainable land management in Asia introducing the landscape approach. - Critchley, William (Asian Development Bank, 2017)
This publication sets out how the landscape approach can contribute to overcoming major environmental and developmental challenges focusing on rural areas of Asia and by examining prevalent forms of SLM (namely participatory forest management, terraces, conservation agriculture, and home gardens). This publication seeks to strengthen awareness of the landscape approach and facilitate the integration of its key elements into cooperation programs with its developing members.